Windows of faith : Muslim women scholar-activists in North America - Webb, Gisela (Women and gender in North American religions., 2000)
"This collection of essays brings together voices from the most recent development in Muslim women's studies, namely, the burgeoning network of Muslim women working on issues of women's human rights through engaged revisionist scholarship in such areas as theology, law and jurisprudence, and women's literature." - BACK COVER.